MODEL OF ASSESSMENT OF CAPABILITIES OF COMBINATORIAL STUDENTS OF TEACHER SCHOOL TEACHER INITIAL SCHOOL - Lora Wahyuni; Yetti Supriyati; Sofia Hartati (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The ability of combinatorial reasoning is part of the formal operational phase that must be owned by college students, the ability to think of solving problems in a way how to analyze the problem. This study aims to assess the ability of combinatorial reasoning by using test questions as a basic biology concept appraisal tool in graduate Education Primary School Teachers. The research method used is research development with Borg and Gall model, which includes gathering information, planning, developing the initial product, field trials, and field operational trials. The instrument used in this research is a questionnaire. Validation is done by material experts, evaluation experts, and linguists. The subjects of this study are students of Primary School Teacher Education. The study was conducted in three stages of one to one test of 8 students, initial field testing of 15 students, and large group trials of 30 students. Data analysis technique in this research is qualitative data analysis and quantitative data analysis. The result of research based on field trials that have been done and the revision of expert percentage average of the whole aspect of 78.43%. Based on observations from 30 students, it can be concluded that combinatorial reasoning capability includes regulatory aspects, finding solutions, classifying with new ideas and solving problems for students Primary school teacher education in basic biology concepts This indicates that test questions can be a tool of ability assessment combinational reasoning. Keywords: combinatorial ability, assessment, development research